HEALTH POLICY AND PLANNING STRATEGY INITIATIVES ON UNIVERSAL HEALTH COVERAGE: A PERSPECTIVE FROM KENYA - KENNEDY ONGOYE, Ogwengo; G., Kamau; N., Gitahi (The Strategic Journal of Business & Change Management, 2022)
Universal health coverage is an important and noble objective for quality healthcare service delivery for all citizens in any country. However, it needs to be anchored on a robust policy framework. Therefore, a strong policy framework is needed to underline the government’s commitment towards this initiative. However, it has not been previously established whether health policies as a strategy significantly affects Universal Health Coverage in Kenya. Therefore, the aim of this paper was to establish the influence of health policy and planning strategy initiatives on achievement of UHC in Kenya. The study adopted a descriptive research design targeting UHC stakeholder organizations including the Ministry of Health, public and private social health insurers, donor fund agencies, as well as public and private healthcare providers in the country. From these, a sample size of 234 organizations were selected using mixed sampling techniques to participate in the study. Data was collected through questionnaires and interview schedules. Data was analyzed using descriptive statistics and inferential statistics, that is, bivariate linear regression analysis. The study found that health policies strategy had a significant relationship with the achievement of the Universal Health Coverage in Kenya. This meant that strengthening health policies will lead to better achievement of UHC. The study recommended that policies aimed at the regulation of the health sector to achieve UHC need to be strengthened so as to improve collaboration among healthcare organizations and the achievement of UHC in the country.
Keywords: Universal Health Coverage; Health Policy; insufficient Funding; Sustainable Health Financing Strategies